Synthesis of New Benzofuran-2-Carboxylic Acid Derivatives - M. Kowalewska; H. Kwiecień; M. Śmist; A. Wrześniewska (Journal of Chemistry)
Novel ethyl ester and methylamide of 5-[bis(2-chloroethyl)amino]-7-methoxybenzofuran-2-carboxylic acid as well as (2-hydroxy-1,1-dimethylethyl)amides of 5-bromo- and 5,7-dichlorobenzofuran-2-carboxylic acid were synthesized and characterized.